Cyber physical systems for occupational safety at industrial sites: opportunities and challenges - Bragatto, Paolo; Ansaldi, Silvia Maria (Serbian Journal of Management, 2022)
In last decade, many Cyber Physical Systems CPSs for occupational safety have been developed within research programs funded by national and transnational bodies. Many of them are now ready for the market.  The paper focuses on the industrial sectors, where the safety of the worker  and the safety of machines, equipment and processes are linked each other. The papers proposes to safety managers criteria and suggestions for choosing appropriate CPS for seizing the great opportunities for safety improvement. The paper discusses a few issues, including cybersecurity and privacy, which are critical for a successful implementation of the CPSs in occupational safety. Safety Management System SMS, in particular, must be adequate to collect the amount of data generated by many sensors distributed in work ambient and worn by workers.
Keywords: Cyber Physical Systems; Occupational Safety; Industrial Safety